Nokia's supply chain management - Walker, Russell, 1972-; Wilson, Joanna ([London] : SAGE, 2016)
In March 2000 a fire broke out at the Royal Philips Electronics plant, damaging its supply of semiconductor chips. Nokia Corporation and Ericsson LM relied on these chips to produce their cell phones; together they received 40 percent of the plant's chip production. Both companies were about to release new cell phone designs that required the chips. At Nokia, word of the setback spread quickly up the chain of command. Nokia's team, which had a crisis plan in place, sprang into action. With an aggressive, multipronged strategy, Nokia avoided any cell phone production loss. In contrast, the low-level technician who received the information at Ericsson did not notify his supervisors about the fire. This case study discusses this topic.
Originally Published in: Walker, R., & Wilson, J. (2012). Nokia's Supply Chain Management. 5-111-007. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Nokia (Firm); Business logistics -- Case studies; Production management -- Case studies